Dopamine alleviates salt‐induced stress in Malus hupehensis. Issue 4 (8th October 2014) - Li, Chao; Sun, Xiangkai; Chang, Cong; Jia, Dongfeng; Wei, Zhiwei; Li, Cuiying; Ma, Fengwang
Abstract : Dopamine mediates many physiological processes in plants. We investigated its role in regulating growth, ion homeostasis and the response to salinity in Malus hupehensis Rehd. Both hydroponics and field‐pot experiments were conducted under saline conditions. Salt‐stressed plants had reduced growth and a marked decline in their net photosynthetic rates, values for Fv / Fm and chlorophyll contents. However, pretreatment with 100 or 200 μ M dopamine significantly alleviated this inhibition and enabled plants to maintain their photosynthetic capacity. In addition to changing stomatal behavior, supplementation with dopamine positively influenced the uptake of K, N, P, S, Cu and Mn ions but had an inhibitory effect on Na and Cl uptake, the balance of which is responsible for managing the response to salinity by Malus plants. Dopamine pretreatment also controlled the burst of hydrogen peroxide, possibly through direct scavenging and by enhancing the activities of antioxidative enzymes and the capacity of the ascorbate–glutathione cycle. We also investigated whether dopamine might regulate salt overly sensitive pathway genes under salinity. Here, MdHKT1, MdNHX1 and MdSOS1 were greatly upregulated in roots and leaves, which possibly contributed to the maintenance of ion homeostasis and, thus, improved salinity resistance in plants exposed earlier to exogenous dopamine. These results support our conclusion that dopamine alleviates salt‐induced stress not only at the level of antioxidant defense but also by regulating other mechanisms of ion homeostasis.